Three-Dimensional Facies Modeling of Deepwater Fan Sandbodies: Outcrop Analog Study from the Miocene Kerek Formation, Western Kendeng Zone (North East Java Basin) - Ferry Andika Cahyo; Octavika Malda; Iqbal Fardiansyah; Carolus Prasetyadi (Berita Sedimentologi, 2013)
Kendeng Zone is well known as the main depocenter in the North East Java Basin. It developed as a back arc basin related to Oligo-Miocene volcanic arc and was subsequently filled with thick pelagic and volcanogenic sediments.This article emphasizes on determination of facies, geometry and distribution of sand bodies within the Miocene Kerek Formation that comprises the western Kendeng Zone. Sedimentological logs and rock samples were collected from outcrop data along river traverses in the study area. The samples were described and characterized by using petrography, paleontology and sedimentology analyses. Three depositional facies were identified, which consist of massive sandstone of submarine lower fan, a lobe of submarine lower fan and pelagic mud deposits.Statistical analysis was also used to characterize and describe identified depositional facies within the Kerek Formation. Statistically, the geometry consists of (1) pebbly massive sandstones of submarine lower fan (mean distribution of sands bodies: 4.58 km, mean thickness: 0.6 m, length from 3D modeling: 1.58 km); (2) sandstone sheets of submarine lower fan (mean distribution of sands bodies: 2.85 km, mean thickness: 0.08 m, length from 3D fence diagram: 1.26 km); (3) pelagic mud, which is composed solely of thick mudstone lithofacies. In term of reservoir potential, the massive sandstones that have significant amount of porosity would be considered as having the highest potential.